Teenager Value in Mark Twain's the Adventure of Tom Sawyer - Hairunisa Nugraheni; Indah Damayanti; Zahrida Zahrida (UNIB Press, 2023)
This research aimed to find out the kind of values in the teenager characters of Mark Twain’s The Adventure of Tom Sawyer as well as to find out its similarities with the character of Indonesian teenager. Library research (documentation) and descriptive qualitative method were used to conduct the research. The data findings were identified by using Peterson and Seligman's virtues and character strengths (2004) then the researcher found out the similarities with the characters of Indonesian teenager based on Indonesia Ministry of Education’s Character Education using checklist and simple tabulation. The results showed that: 1) There were 22 type of values found in the teenager characters of Mark Twain’s The Adventure of Tom Sawyer namely curiosity, creativity, open-mindedness, love of learning, wisdom, bravery, honesty, persistence, vitality, love, kindness, social intelligence, fairness, leadership, humility, prudence, self-regulation, appreciation of beauty and excellence, gratitude, hope, humor, and spirituality; 2) There were six similar traits that are presented in 22 type of values found in the teenager characters and characters of Indonesian teenager (Character Education) namely religious, honest, creative, curiosity, love to read, and care about social. To conclude, there were two points about this research as follows. 1) Teenager characters of Mark Twain’s The Adventure of Tom Sawyer dominantly had good personality based on Peterson and Seligman’s virtue and character strengths. 2) There were six similar values (religious, honest, creative, curiosity, love to read, and care about social) between the characters of Indonesian teenager and teenager values from Mark Twain’s The Adventure of Tom Sawyer.